Cell-autonomous reduction of CYFIP2 is insufficient to induce Alzheimer's disease-like pathologies in the hippocampal CA1 pyramidal neurons of aged mice. Issue 1 (11th December 2023) - Ma, Ruiying; Zhang, Yinhua; Li, Huiling; Kang, Hyae Rim; Kim, Yoonhee; Han, Kihoon
ABSTRACT : Cytoplasmic FMR1-interacting protein 2 (CYFIP2) is an evolutionarily conserved multifunctional protein that regulates the neuronal actin cytoskeleton, mRNA translation and transport, and mitochondrial morphology and function. Supporting its critical roles in proper neuronal development and function, human genetic studies have repeatedly identified variants of the CYFIP2 gene in individuals diagnosed with neurodevelopmental disorders. Notably, a few recent studies have also suggested a mechanistic link between reduced CYFIP2 level and Alzheimer's disease (AD). Specifically, in the hippocampus of 12-month-old Cyfip2 heterozygous mice, several AD-like pathologies were identified, including increased levels of Tau phosphorylation and gliosis, and loss of dendritic spines in CA1 pyramidal neurons. However, detailed pathogenic mechanisms, such as cell types and their circuits where the pathologies originate, remain unknown for AD-like pathologies caused by CYFIP2 reduction. In this study, we aimed to address this issue by examining whether the cell-autonomous reduction of CYFIP2 in CA1 excitatory pyramidal neurons is sufficient to induce AD-like phenotypes in the hippocampus. We performed immunohistochemical, morphological, and biochemical analyses in 12-month-old Cyfip2 conditional knock-out mice, which have postnatally reduced CYFIP2 expression level in CA1, but not in CA3, excitatory pyramidal neurons of the hippocampus. Unexpectedly, we could not find any significant AD-like phenotype, suggesting that the CA1 excitatory neuron-specific reduction of CYFIP2 level is insufficient to lead to AD-like pathologies in the hippocampus. Therefore, we propose that CYFIP2 reduction in other neurons and/or their synaptic connections with CA1 pyramidal neurons may be critically involved in the hippocampal AD-like phenotypes of Cyfip2 heterozygous mice.